2018
DOI: 10.1002/jcp.26371
|View full text |Cite
|
Sign up to set email alerts
|

The long noncoding RNA NEAT1 contributes to hepatocellular carcinoma development by sponging miR‐485 and enhancing the expression of the STAT3

Abstract: Accumulating evidence has supported the significance of lncRNAs in tumorigenesis. Recently, some studies indicate the oncogenic role of lncRNA Nuclear Enriched Abundant Transcript 1 (NEAT1) in hepatocellular carcinoma (HCC). In our present study, we focused on the biological mechanisms through which NEAT1 can regulate HCC development. We found that NEAT1 was greatly upregulated in human HCC cell lines including Huh7, Hep3B, HepG2, Bel-7404, and SK-Hep1 cells compared to the normal human liver cell line LO2. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 29 publications
3
53
0
Order By: Relevance
“…Mechanistically, upregulation of NEAT1 in GSCs under ADV infection could be attributed to TLR9 activation, and knockdown of NEAT1 was accompanied by an inhibition of STAT3 expression and phosphorylation. This is consistent with several reports showing that NEAT1 promotes cancer progression by enhancing STAT3 signaling [48][49][50] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Mechanistically, upregulation of NEAT1 in GSCs under ADV infection could be attributed to TLR9 activation, and knockdown of NEAT1 was accompanied by an inhibition of STAT3 expression and phosphorylation. This is consistent with several reports showing that NEAT1 promotes cancer progression by enhancing STAT3 signaling [48][49][50] .…”
Section: Discussionsupporting
confidence: 93%
“…These results, in combination with literatures, suggested that NEAT1 is downstream to TLR9-MYD88 and regulates STAT3 46,[48][49][50] .…”
Section: Neat1 Is Associated With Activation Of Tlr-stat Pathway In Gsupporting
confidence: 81%
“…For example, NEAT1 can regulate gastric progression via targeting miR‐335‐5p/ROCK1 axis . NEAT1 can contribute to hepatocellular carcinoma development through sponging miR‐485 and activating STAT3 . Knockdown of NEAT1 inhibits osteosarcoma progression by sponging miR‐194 …”
Section: Introductionmentioning
confidence: 99%
“…Then, we focused on the potential molecular mechanism of NEAT1 in LUAD. Previous studies have demonstrated that NEAT1 promoted tumor development by functioning as a ceRNA or a molecular sponge to bind to miRNA and subsequently regulate cancer-related gene expression [35][36][37][38]. In this study, we probed the interaction between NEAT1 and miR-193a-3p.…”
Section: Discussionmentioning
confidence: 99%